Comparative analysis of eco port policies in Egypt and Indonesia - Andriyanto, Dimas; Koestoer, Raldi Hendrotoro Seputro (Ex Aequo Et Bono Journal Of Law, 2024)
Activities at the port can cause damage to the environment. The impact can occur on air quality, water, and noise, to produce waste. Environmental damage at the port needs to be handled by managing the port in an environmentally sound manner that prioritizes environmentally, economically, and socially sustainable principles. The concept of ecologically friendly ports has been implemented in Egypt at Damietta Port and in Indonesia at the Nizam Zachman Ocean Fishing Port. This study analyzes the comparison of two ports in the two countries based on the implementation of eco-port policies and determines the positive and negative sides of the policy. Literature and comparative studies on the performance of eco ports were carried out for this research by analyzing the relevant theoretical basis from scientific journals, websites, and reports from related institutions. Based on the literature review analysis, Damietta Port in Egypt and the Ocean Fishery Port of Nizam Zachman Indonesia have implemented the eco port concept in managing their seaports. However, several positive and negative impacts must be addressed from implementing this policy based on environmental policy regulations, technical benefits, economic benefits, and humans.